Delteil's Les Écœurés: Gilets Jaunes and the Limits of the Noir. - Goulet, Andrea; Lee, Susanna; Singh, Lisa; Sobanet, Andrew (Contemporary French & Francophone Studies, 2022)
This article is an interdisciplinary study of Gérard Delteil's Les Écœurés, a 2019 novel that was marketed as a "le premier polar en Gilet Jaune." In this essay, we explore the generic tensions that arise when murder mystery intersects with socioeconomic criticism in our age of advanced capitalism. We argue that Les Écœurés functions differently when read through a sociological prism than it does as a noir or polar. We demonstrate that analysis of social media data shows that Delteil captures quite well and to a large extent reproduces the concerns of the Gilets Jaunes movement, while at the same time showcasing the dispiriting durability of a corrupt establishment. Second, on the level of character, we maintain that in presenting a drably failed bildungsroman, the novel undercuts the importance of any individual agency or élan. And third, we argue that on the level of genre, the text—by sidelining its own murder mystery—raises questions about the force and relevance of crime fiction as a potential agent of social change. Ultimately, we maintain that the very failures in and of Les Écœurés point metatextually to the novel's position as an artifact of the period and as embodiment of the Gilets Jaunes movement's likely fate.